Pengembangan Usaha Penetasan Telur Itik “Regra Hatchery” di Nagari Lubuk Tarok Kabupaten Sijunjung - Montesqrit Montesqrit; Haris Suryamen; Aprizal Aprizal (Warta Pengabdian Andalas, 2021)
The RegRa farm and hatchery in Lubuk Tarok, Sijunjung Regency, West Sumatra, has started a duck egg hatchery business. The hatchery business is not following good standards and has not brought high profits. This is because the hatchability of the eggs produced is still low; it takes time every day to turn the eggs over; the size of ducklings is many small, and the fertile eggs to be hatched are still purchased from other places. The community engagement team gave the solution for this problem: renovating the hatching machine with automatic egg turning, repairing the enlargement cage, renovating the cage, and caring for the ducklings. The solutions offered were carried out well by partners. As a result, the hatchability of eggs increases, the ducklings sold are healthy and agile, and there is a desire to raise ducklings to produce their fertile eggs in the future.